Wnt7b Inhibits Osteoclastogenesis via AKT Activation and Glucose Metabolic Rewiring - Wu, Fanzi; Li, Boer; Hu, Xuchen; Yu, Fanyuan; Shi, Yu; Ye, Ling (Frontiers in Cell and Developmental Biology, 2021)
The imbalance between bone formation and bone resorption causes osteoporosis, which leads to severe bone fractures. It is known that increases in osteoclast numbers and activities are the main reasons for increasing bone resorption. Although extensive studies have investigated the regulation of osteoclastogenesis of bone marrow macrophages (BMMs), new pharmacological avenues still need to be unveiled for clinical purpose. Wnt ligands have been widely demonstrated as stimulators of bone formation; however, the inhibitory effect of the Wnt pathway in osteoclastogenesis is largely unknown. Here, we demonstrate that Wnt7b, a potent Wnt ligand that enhances bone formation and increases bone mass, also abolishes osteoclastogenesis in vitro. Importantly, enforced expression of Wnt in bone marrow macrophage lineage cells significantly disrupts osteoclast formation and activity, which leads to a dramatic increase in bone mass. Mechanistically, Wnt7b impacts the glucose metabolic process and AKT activation during osteoclastogenesis. Thus, we demonstrate that Wnt7b diminishes osteoclast formation, which will be beneficial for osteoporosis therapy in the future.